SOSIALISASI ACTIVE LEARNING MATEMATIKA MELALUI PERMAINAN KARTU BAGI GURU-GURU SD N 69 KOTA BENGKULU - Nurul Astuty Yensy (Universitas Bengkulu, 2019)
The majority of teacher in SD N 69 Bengkulu city still have difficulty how to organize the effective learning. Very rarely do they plan mathematic learning with a real-life approach that enable the student, because they assume that such learning was useless, confusing and time-consuming. Based on the preliminary survey found that in SD N 69 Bengkulu city, the teacher in there still used a conventional method in learning. The teacher rarely used the prop as learning media, as in the matter of multiplication of integers. Whereas making innovative and creative mathematical tool was so easy to be created, so that in this activity have done